IJTIHAD DAN PENERAPANNYA DALAM EKONOMI KEUANGAN - Hutagalung, Syahrial Arif; Annisa Afwani; Dinda Nurayuni Humaira; Muhammad Abdillah Pratama; Sherin Aulia Putri; Stefani (Journal of Global Islamic Economic Studies, 2023)
This research discusses the role of ijtihad in the innovation of Islamic banking and finance products, focusing on products such as Sukuk and Murabahah. Ijtihad is important in developing these products to be in accordance with sharia principles, especially in facing the challenges of the conventional financial system based on riba. Sukuk, as an alternative to conventional bonds, is based on the ownership of real assets, while Murabahah is a financing method that does not involve interest. In addition, this paper also highlights the challenges faced by sharia fintechs, particularly in the P2P lending model, which requires ijtihad to ensure compliance with sharia principles. The author emphasizes the importance of general principles in muamalah, such as the prohibition of usury and tyranny, as well as the need for careful ijtihad to maintain the relevance of Islamic financial products to the needs of the times. Obstacles in the ijtihad process, including differences of opinion among scholars, the complexity of modern financial products, and limited resources, were also discussed. In addition, the role of women in contemporary ijtihad is recognized as an important contribution in providing new perspectives and fighting for gender justice.